Amak interview and stories - Ama; Lidiia Yapkingina; Valentina Dedyk; Anatoly Sorokin (Alexander King, 2013)
Amak is wearing her (great?) grandmother's Even coat with traditional apron, which is preserved as a family heirloom in their home. Her grandson Tololo is sitting next to her for the first part of the video. She is interviewed about her life, tells several legends and stories and sings. There is some drumming and singing near the end. The last woman to drum is Ira, the nurse. Ambient audio recording for video. Left and right channels were swapped from original recording because I had Tascam set incorrectly with mics spread wide. This file has the correct L-R sound space. Son is Stasik, who lives with Ama and Maksim Plepa. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra. Also fluent (listening, reading, some writing/speaking) in English and Japanese. Alutor level is elementary.